2008
DOI: 10.1071/ah080570
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment clients' readiness for hepatitis C treatment: implications for expanding treatment services in drug and alcohol settings

Abstract: This study explores the perception of and readiness for hepatitis C treatment within a sample of 77 clients already participating in drug treatment, with a view to identifying likely barriers and incentives to hepatitis C treatment within a drug treatment population. Participants with hepatitis C did not demonstrate a consistent, indepth knowledge of the infection, lacked confidence in symptom recognition, and had little awareness of treatment options. Those without obvious symptoms or liver deterioration did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…A review of the literature highlights ‘readiness’ as an important construct in an individual's decision-making to undergo treatment but there is little consensus on its definition [19][21]. In one study, people with addictive behaviours were found to move through the following stages of readiness and change: from pre-contemplation (no intention to change) → contemplation (thinking of change) → preparation for action (behaviour, experiences or environment) → maintenance (prevent relapse and consolidate gains) [22].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature highlights ‘readiness’ as an important construct in an individual's decision-making to undergo treatment but there is little consensus on its definition [19][21]. In one study, people with addictive behaviours were found to move through the following stages of readiness and change: from pre-contemplation (no intention to change) → contemplation (thinking of change) → preparation for action (behaviour, experiences or environment) → maintenance (prevent relapse and consolidate gains) [22].…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, reasons for patients in OMT not wanting HCV treatment are mainly having heard stories about side effects; absence of symptoms; and lack of information about treatment options [18,22]. These reasons might be applicable to our results: The number of patients reporting knowing something about HCV treatment increased significantly from baseline to follow-up six months later.…”
Section: Discussionmentioning
confidence: 44%
“…The purpose of OMT service is not only to treat drug dependence, but also to notify problems concerning the patients' somatic health. This could be further stressed by encouraging the individual with more information, motivational interviewing etcetera, as supported by previous research [21,22]. It is also important to create structures in the health care system which facilitates quick and easy referral from OMT to HCV treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the international awareness about the long-term consequences of HCV and recent shifts in guidelines related to antiviral therapy for patient in OAT recipients, only a minority are enrolled in antiviral therapy (McCormick et al, 2008;Treloar and Holt, 2008). In our study, less than a quarter of a preselected sample eventually initiated treatment.…”
Section: Discussionmentioning
confidence: 72%